Spór o Puszczę Białowieską w świetle sporu o ochronę przyrody na świecie - Witkowski, Zbigniew (Leśne Prace Badawcze, 2017)
The controversy between naturalists and foresters on the management of the Białowieża Forest is one of numerous disputes in conservation biology. Cause of the dispute is a difference in stand-point on the purpose of nature conservation. Biocentrists (Soulé 1985) argue that the only goal should be to preserve natural processes as well as endangered ecosystems and species. Anthropocentrists on the other hand (Kareiva, Marvier 2012) support conservation as a need of mankind, i.e. the sustainable support of ecosystem services with the protection of species and ecosystems simply being a side effect. Another important factor in the dispute is the management of bark beetle mass outbreaks. Foresters try to control by removing the infested trees, but naturalists protest against this practice. However, in 2013 the European Commission clearly presented its statement in this regard (EU Guidelines on Wilderness in Natura 2000) and thus the dispute has only shown that none of the debating parties are familiar with the EU guidelines. According to the author, the more serious problem of messy organization of the Białowieża Forest conservation is rarely raised in the dispute. Multiple protected areas were established in the forest based on six different law forms for nature conservation and two forms of international origin. Such surplus of forms and areas leads to chaos and hinders the management of this valuable area.